A experiência desenvolvimentista brasileira a partir de 2003 - RIBEIRO FILHO , Wilson França (2019)
This dissertation aims to expose and discuss the performance of the Brazilian developmental experience starting in 2003, with the inauguration of Luiz Inácio Lula da Silva as President of the Federative Republic of Brazil. In this exposition, the analysis is based on the presentation of some economic indicators, whose purpose is to try to approach the empirical validation of economic development in this period, and from the perspective of the ideology of development, and how it contributed to the beginning, and end of the Brazilian developmental experience. Therefore, the structuring of this work consists of three parts, besides the introduction and the final considerations, which consubstantiates the achievement of the Brazilian developmental experience. The first section approaches the concept of ideology, starting from the Marxian view of false consciousness until the continuation of a broader concept, involving the contributions of Antonio Gramsci and György Lukács, and ends by correlating ideology with development in its phenomenal conception. The second section aims at exposing the economic development theories developed in the XXI century that are theoretically and methodologically linked to the Brazilian experience. It is subdivided into two parts, in which the first deals with the theoretical contributions of development elaborated in the context of the developed countries and the second subsection refers to the contribution of ECLAC in the formulation of a proper theory for economic development in Latin America. Finally, the last section is entitled to the exposition and discussion of the Brazilian developmentalist experience, under the economic-ideological bias, taking into account the inauguration of Luiz Inácio Lula da Silva as President of the Republic, in order to connect the Brazilian economic performance in this developmental period and the exercise of ideological thought as a way of reproducing, leading and legitimizing economic development in Brazil. In the final considerations, some considerations and reflections about the period presented are drawn.